The influence of the Target of Rapamycin (TOR) on starch metabolism in Arabidopsis thaliana - Araujo, Elias Feitosa (2016)
Plant growth and development are maintained by a complex network controlled by environmental factors including the availability of water, light and nutrients and by several signaling pathways. One of the most important signaling pathways, conserved in eukaryotes, is the kinase Target of Rapamycin (TOR). Various lines of evidence point out that TOR plays a fundamental role in carbon and nitrogen balance, acting as an essential regulator on central metabolism by controlling growth and biomass production. Starch is the major form of carbon storage and its content is negatively correlated with growth. Transgenic lines with reduced expression of TOR gene or components of the TOR complex present a clear starch excess phenotype. However, it remained to be elucidated whether the accumulation of starch is due to increased synthesis, impaired degradation or both. In this work, Arabidopsis seedlings treated with the specific ATP-competitive inhibitor of TOR kinase AZD-8055 showed a starch excess phenotype right after 4 hours of treatment and the accumulation of starch was proved to be due to an augmentation in the rate of starch synthesis. Furthermore, TOR- inhibited plants presented an average increase of 20-30% in their starch content at the end of day when compared to control. Metabolite profiling analysis showed that TOR– inhibited plants exhibited broad changes in the levels of sucrose, fructose, glucose, maltose, mannose and orthophosphate, which are associated directly or indirectly with starch metabolism. In addition, a correlation between the amount of mannose, orthophosphate and increased starch content was noticed in AZD-treated plants. Gene expression analysis of AGPase subunits showed significant changes only from 18 and 24h after treatment. Although TOR inhibited plants displayed higher content of the active form of AGPase (monomer), enzymatic activity assays revealed that changes in AGPase activity might occur as secondary effect of TOR inhibition and might be not related to the starch excess phenotype observed 4 hours after AZD-treament. Since several enzymes related to starch metabolism are subject to redox regulation, the levels of glutathione were measured to verify the redox environment of the cells. TOR- inhibited plants showed changes in the pools of glutathione, mainly in its reduced form, and the redox state of the cells tended to be more reduced. Together, these results indicate the participation of TOR signalling on starch metabolism but the mechanistic behind this process need further studies.